2009
DOI: 10.1002/jor.20695
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic and myogenic gene expression in rotator cuff muscle of the sheep after tendon tear

Abstract: Chronic rotator cuff tendon tears lead to fatty infiltration and muscle atrophy with impaired physiological functions of the affected muscles. However, the cellular and molecular mechanisms of corresponding pathophysiological processes remain unknown. The purpose of this study was to characterize the expression pattern of adipogenic (PPARg, C/EBPb) and myogenic (myostatin, myogenin, Myf-5) transcription factors in infraspinatus muscle of sheep after tenotomy, implantation of a tension device, refixation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
59
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 35 publications
8
59
0
2
Order By: Relevance
“…Adipogenic transcription factors have been considered key regulators for fatty degeneration of muscle after RCT. One research group reported that the transcription factors PPARγ, C/EBPβ, and Myf‐5 play crucial roles in impairment and regeneration of rotator cuff muscles after tendon tears in a sheep model 8. Joshi et al suggested that mammalian target of rapamycin signaling plays an important role in muscle atrophy after massive RCTs in a rat model and mediates rotator cuff fatty infiltration via SREBP‐1 and PPARγ 23.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adipogenic transcription factors have been considered key regulators for fatty degeneration of muscle after RCT. One research group reported that the transcription factors PPARγ, C/EBPβ, and Myf‐5 play crucial roles in impairment and regeneration of rotator cuff muscles after tendon tears in a sheep model 8. Joshi et al suggested that mammalian target of rapamycin signaling plays an important role in muscle atrophy after massive RCTs in a rat model and mediates rotator cuff fatty infiltration via SREBP‐1 and PPARγ 23.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RCT could be considered a good model to understand age‐associated muscle fatty infiltration. To date, the mechanism of muscle fatty infiltration in RCT has been investigated using various animal models 8, 9, 10, 11, 12, 13. However, the molecular mechanisms underlying rotator cuff muscle atrophy and fatty infiltration remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 CCAAT/ enhancer-binding proteins (C/EBPs) and the peroxisome proliferator-activated receptors (PPARs), members of two families of transcription factors, have been implicated in the differentiation of preadipocytes into mature adipocytes. 10 Frey et al 11 reported an upregulation of adipogenic transcription factors after experimental chronic rotator cuff tear. However, in the rotator cuff muscles, the molecular mechanism of the differentiation of muscle progenitors into adipocytes has not been fully clarified yet.…”
mentioning
confidence: 99%